2018
DOI: 10.2337/db17-1323
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and Immunity Pathways Regulate Genetic Susceptibility to Diabetic Nephropathy

Abstract: Diabetic nephropathy (DN) is a leading cause of end-stage renal disease worldwide, but its molecular pathogenesis is not well defined, and there are no specific treatments. In humans, there is a strong genetic component determining susceptibility to DN. However, specific genes controlling DN susceptibility in humans have not been identified. In this study, we describe a mouse model combining type 1 diabetes with activation of the renin-angiotensin system (RAS), which develops robust kidney disease with feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 54 publications
3
30
0
Order By: Relevance
“…1 DM is associated with severe damage to multiple organ systems, such as the heart, eyes, and kidneys. [2][3][4] Recently, increasing attention has been paid to the pathological changes in the brain induced by DM. Diabetes-induced brain injury manifests as neurodegeneration, cerebral infarction, and progressive cognitive decline.…”
Section: Introductionmentioning
confidence: 99%
“…1 DM is associated with severe damage to multiple organ systems, such as the heart, eyes, and kidneys. [2][3][4] Recently, increasing attention has been paid to the pathological changes in the brain induced by DM. Diabetes-induced brain injury manifests as neurodegeneration, cerebral infarction, and progressive cognitive decline.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that there might be a strong effect of genetic susceptibility to in uence development of DKD in both animal [25][26][27] and human beings [28,29]. Gurley and his colleagues found a marked triggering of immune and in ammatory gene expression pro les in the mice with DM was associated with susceptibility to development of DKD [8]. Given the fact that hs-CRP is one of the in ammatory biomarkers, the aforementioned ndings, at least partly, support our current results that hs-CRP modi ed the association of blood glucose and DKD.…”
Section: Discussionmentioning
confidence: 99%
“…In one animal experiment, there existed a marked triggering of immune and in ammatory gene expression pro les in the diabetic mice that developed DKD; by contrast, these pathways were coordinately down-regulated in the counterparts protected from kidney injury, suggesting in ammation and immune responsiveness may be critical features determining susceptibility of DKD [7,8]. Several clinical studies also showed activation in ammatory biomarkers, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In our review of the literature, changes in TNF levels are not fully recapitulated in mouse DKD models. A recent paper by Gurley et al (8) proposed that an immune/ cytokine expression profile can also distinguish susceptible and resistant strains of mice, indicating that TNF activation might be an indicator of kidney disease susceptibility in mice as well. Although TNF is a key disease biomarker in patients with diabetes mellitus, the mechanism of TNF activation is unclear.…”
Section: Introductionmentioning
confidence: 99%